Geographic distribution and associated environments characterization of trichilia catigua A. Juss - Meliaceae in Santa Catarina State - Brazil - Júnior, C. Correa (My University, 2002)
A survey was conducted aiming to recognize and characterize the environments of occurrence of Trichilia species and their geographic distribuition, particulary T. catigua A. Juss, in Santa Catarina State. These informations will support a domestication strategy for agricultural production of this spcies. This species is widely used by traditional communities as dye and tonic beverage, as well as digestive and purgative. Some pharmaceutical and beverage industries in Brasil use bark of this species to prepare a tonic drink. There are several common names reffering the species and this situation can promove mistakes in collecting and selling processes. Termperature, soil, vegetational types and edaphoclimatic aspects have great influence on the occurrence of this species. Plant collection strategu was based on herbaria data and field verification. The vouchers were deposited at the Federal University of Parana herbarium (UPCB). The collection sites were geographically located, by latitude and longitude and these data were crossed with climate, soil, temperature, rainfall, altitude and vegetation maps. Catuaba occurs predominantly on a stational semidecidual forest and also on transitional forest with Araucaria and part of Atlantic forest. It is found growing in lower canopy, with fertile soils, and high content of organic matter. The main geomorphological formation are basaltic and the soil types vary from dark red latossol to yellow red latossol, including structured red latossl and cambissol from basaltic and granitic origin.
Keywords: Environmental characterization; Geographic distribuition; Trichilia catigua